Watching TV Series with Horror Content: Audience Attributes, Motivations, Involvement and Enjoyment. Issue 4 (2nd October 2017) - Lin, Carolyn A.; Xu, Zhan
Abstract : This study is the first to explore the motivational, cognitive, affective, and personality factors that influence the enjoyment of and exposure to TV series with horror content. The most-watched TV series identified by 411 study participants were examined in the study. Results indicate that personality traits significantly predict cognitive and affective involvement with these programs and viewing motivations. Viewing motivations significantly influence viewers' cognitive and affective involvement with these TV series as well as their viewing enjoyment and frequency. While positive affect and negative affect are significant predictors of viewing enjoyment, viewing enjoyment has a positive effect on viewing frequency.